Harmonizing early intervention strategies: scoping review of clinical high risk for psychosis and borderline personality disorder - Lo Buglio, Gabriele; Boldrini, Tommaso; Polari, Andrea; Fiorentino, Flavia; Nelson, Barnaby; Solmi, Marco; Lingiardi, Vittorio; Tanzilli, Annalisa (Frontiers in Psychology, 2024)
Aims: To map studies assessing both clinical high risk for psychosis (CHR-P) and borderline personality disorder (BPD) in clinical samples, focusing on clinical/research/preventive paradigms and proposing informed research recommendations. Methods: We conducted a PRISMA-ScR/JBIcompliant scoping review (protocol:https://osf.io/8mz7a) of primary research studies (crosssectional/longitudinal designs) using valid measures/criteria to assess CHR-P and BPD (threshold/subthreshold) in clinical samples, reporting on CHR-P/psychotic symptoms and personality disorder(s) in the title/abstract/keywords, identified in Web of Science/PubMed/(EBSCO)PsycINFO until 23/08/2023. Results: 33 studies were included and categorized into four themes reflecting their respective clinical/research/preventive paradigm: (i) BPD as a comorbidity in CHR-P youth (k = 20), emphasizing early detection and intervention in psychosis; (ii) attenuated psychosis syndrome (APS) as a comorbidity among BPD inpatients (k = 2) with a focus on hospitalized adolescents/young adults admitted for non-psychotic mental disorders; (iii) mixed samples (k = 7), including descriptions of early intervention services and referral pathways; (iv) transdiagnostic approaches (k = 4) highlighting "clinical high at risk mental state" (CHARMS) criteria to identify a pluripotent risk state for severe mental disorders. Conclusion: The scoping review reveals diverse approaches to clinical care for CHR-P and BPD, with no unified treatment strategies. Recommendations for Future research should focus on: (i) exploring referral pathways across early intervention clinics to promote timely intervention; (ii) enhancing early detection strategies in innovative settings such as emergency departments; (iii) improving mental health literacy to facilitate help-seeking behaviors; (iv) analysing comorbid disorders as complex systems to better understand and target early psychopathology; (v) investigating prospective risk for BPD; (vi) developing transdiagnostic interventions; (vii) engaging youth with lived experience of comorbidity to gain insight on their subjective experience; (viii) understanding caregiver burden to craft family-focused interventions; (ix) expanding research in underrepresented regions such as Codice campo modificato Africa and Asia, and; (x) evaluating the cost-effectiveness of early interventions to determine scalability across different countries.